Advancing HEIs' third-mission through dynamic capabilities: the role of leadership and agreement on vision and goals - Audrey Stolze; Klaus Sailer (The Journal of Technology Transfer, 2021)
Higher education institutions (HEIs), once considered among society's most resilient institutions, are facing challenges due to changes in governments' and society's expectations of them. Within the sector, there is a global call for new models and practices, requiring HEIs to develop the management capabilities once reserved for businesses. In this sense, they will pave entrepreneurial pathways and contribute to economic, technological and societal developments in their regions, thus adding a third mission (engaging socio-economic needs and market demands) to the traditional two (education and research) and transforming themselves into more entrepreneurial institutions. Dynamic capabilities enable transformation processes by allowing the dynamic sensing and seizing of opportunities and risks and the promotion of iterative change and reconfiguration. Scholars have called on HEIs to develop such dynamic capabilities in order to transform themselves and better respond to their sector's challenges. Nevertheless, the understanding of how dynamic capabilities might advance HEIs' third mission is still an underexplored concept, and in this paper, we propose mechanisms that promise to transform dynamic capabilities into third mission advancement. We have developed numerous theoretically grounded hypotheses and tested them with a partial least squares structural equation model into which we funnelled data collected from key decision-makers at German HEIs. The results suggest that dynamic capabilities do indeed influence third mission advancement; however, this relationship is mediated by the role of leadership and organisational agreement on vision and goals.
Keywords: I23; O30; 600; Entrepreneurial universities; Third mission; Strategic management; Dynamic capabilities; Leadership; Vision and goals